Upaya Meningkatkan Hasil Belajar PAI melalui Model PBL di Kelas VI SDN 21 Pakan Sinayan Kabupaten Agam - Ramadani Yusnita; Rahmiwati Rahmiwati (Kampus Akademik Publiser, 2024)
This study aims to obtain information and improve student learning outcomes in Islamic religious education by using the problem-based learning model in grade VI of SDN 21 Pakan Sinayan, Agam Regency. This study is a Classroom Action Research, with the research subjects being 11 students in grade VI. The research data was collected using observation, field notes, learning outcome test sheets, and documentation in cycles I and II. The data obtained was analyzed using percentage analysis. The results of the study related to learning outcomes showed that this demonstration learning model can improve student learning outcomes, because students have successfully achieved the predetermined minimum competency standard (KKM). This can be proven by the increase in student learning completeness in each cycle, namely Cycle I (48%) and Cycle II (80%).